An emergency rescue communication system and environmental monitoring subsystem for underground coal mine based on wireless mesh network - Haojiang Zhao; Wei Yang (International Journal of Distributed Sensor Networks, 2018)
According to the characteristics of the underground coal mine roadway structure and disaster environment, this article proposes an underground emergency rescue communication system based on wireless mesh network and its corresponding environmental monitoring subsystem. We design the structures of the emergency rescue communication system and the wireless mesh nodes. The nodes are designed with intrinsic safety features. The work also develops wireless multi-parameter environmental monitoring terminals, and sets up the software platform for the environmental monitoring subsystem. The developed underground coal mine emergency rescue communication system based on wireless mesh network and environmental monitoring subsystem are tested both on the ground and in a real underground roadway environment. Experimental results from the testing show that the signal strength is -45 dBm on average, and the bandwidth attenuation of each hop is less than 10%, the transmission delay after the 11th hop is only 14 ms. The developed emergency rescue communication system is functionally stable, the environmental monitoring subsystem is capable of performing real-time monitoring of various underground environmental parameters, and achieves high accuracy in monitoring.